Enhancing continued professional development strategically : an outlook via adult learning theory / Fadilah Puteh and Maniam Kaliannan - Puteh, Fadilah; Kaliannan, Maniam (Universiti Teknologi MARA, Shah Alam, 2016)
Professional development (PD) among organizational talents is a critical element in today’s business environment. In view of PD, both organizations and their professional members are required to learn continuously, thus Continued Professional Development (CPD) activities in organizations are gaining prominence. Formal, non-formal and informal learning constitute CPD learning dimensions. Given that professionals are experienced individuals, their learning needs and situations differ from conventional learners. Adult learners are found to be highly motivated, self-directed and very aware of their personal strengths, tend to choose knowledge that is meaningful to them and relate that with their experiences. The theory of adult learning (ALT) suggests that adult learners or working persons have certain characteristics that differentiate them from conventional learners. However, several studies revealed that learning activities to cater for PD are inconsistent with adult learning principles. The adult learners are mostly treated no different than the conventional learners; hence knowledge transfer did not reach its optimal expectations. On that note, this article discusses CPD activities from adult learning perspective gathered from extensive literatures. The objectives of this paper are threefold. First, this paper explains the importance of CPD from the adult learning standpoint. Second, this paper analyses the extent of CPD activities in fulfilling adult learning principles. Lastly, this paper proposes a feasible strategic CPD framework for future research.